P253 Pulmonary infiltrates in HIV negative immunocompromised patients: outcome and predictive factors. (16th November 2010) - Chandramouli, S; Devine, M; Shoo, H; Duffy, N
Abstract : Introduction: The incidence of pulmonary complications in immunocompromised patients is on the rise mainly driven by increased organ and bone marrow transplants, more aggressive chemotherapy and novel immunosuppressants.1 Mortality rates in HIV negative immunosuppressed patients vary between 40–85%.1–3 Prognostic factors have been previously described in these patients and these include need for mechanical ventilation and delay in diagnosis.2 Aims: To describe the characteristics of immunocompromised HIV negative patients presenting with pulmonary infiltrates and to examine the factors that lead to increased mortality. Methods: All HIV negative immunocompromised patients who had bronchoalveolar (BAL) samples taken from January 2007 to January 2010 were identified from laboratory data. Their baseline demographics, immune status, clinical presentation, radiological picture and blood results at the time of BAL sampling were obtained from hospital records. The influence of various categorical variables on mortality was evaluated using Chi-square test. Logistic regression was then used to quantify the impact of each of these variables and obtain OR. Results: 87 patients (33 women) with a median (range) age of 62 (21–87) years were studied. Overall mortality was 49% (42 patients). The Abstract P253 Table 1 shows the effect of different variables on mortality. This was not affected by sex, transplant status or laboratory parameters. With logistic regression analysis, we found that haematological malignancies (OR 7.44, 1.96–28.20), long term steroids (OR 7.87, 2.36–26.20) and age >65 years (OR 3.94, 1.36–11.40) were significantly associated with mortality. The relationship with immunosuppressive drugs was less significant. Conclusions: HIV negative immunocompromised patients with pulmonary infiltrates are more likely to die if they have a haematological malignancy, are on long term steroid therapy or aged >65 years. The effect of immunosuppressive drugs needs more elucidation. Careful attention needs to be paid to these groups of patients to pick up early signs of deterioration.